1994
DOI: 10.1111/j.1365-2958.1994.tb01043.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of rpoS (katF) in oxyR‐independent regulation of hydroperoxidase I in Escherichia coli

Abstract: We present evidence showing that rpoS (katF) is a regulator of katG gene transcription in an oxyR-independent manner. Mutation of the rpoS gene in several different Escherichia coli strains caused a significant reduction in catalase HPI activity. In rpoS-delta oxyR double mutants, the level of HPI was considerably lower compared to the delta oxyR parent strain, and was restored when transformed with an rpoS+ plasmid. Overproduction of HPI in oxyR- suppressor strains was greatly diminished after inactivation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
75
1

Year Published

1995
1995
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(83 citation statements)
references
References 23 publications
5
75
1
Order By: Relevance
“…This result supported the hypothesis that catalase I activity increased in response to elevated oxidative stress in the catalase II-deficient cells 18 . In summary, the data presented here suggests the existence of a secondary pathway for catalase I induction at the stationary phase of B. pseudomallei.…”
Section: Scienceasia Scienceasia Scienceasiasupporting
confidence: 87%
See 1 more Smart Citation
“…This result supported the hypothesis that catalase I activity increased in response to elevated oxidative stress in the catalase II-deficient cells 18 . In summary, the data presented here suggests the existence of a secondary pathway for catalase I induction at the stationary phase of B. pseudomallei.…”
Section: Scienceasia Scienceasia Scienceasiasupporting
confidence: 87%
“…However, in this study we have cultured the bacteria in LB medium and found that at 72 and 96 h, the rpoS mutant strain showed a 31% and 29% survival rate (data not shown), indicating that cells in late stationary phase in rich media had a higher survival rate compared to those grown in minimal media. In E. coli, an increase of HPI catalase activity in stationary phase, attributed to RpoS-dependent transcription of katG has been reported 18 . In the rpoS mutants, these authors 15 detected little or no catalase activities by zymography assays.…”
Section: Discussionmentioning
confidence: 96%
“…The two E. coli hydroperoxidases (catalases) were used as 'reporter genes' for RpoS-dependent transcription because both hydroperoxidase I (katG gene product, cytoplasmic membrane associated) and hydroperoxidase II (katE gene product, present in the cytosol) were shown to be regulated by s s (Ivanova et al, 1994), with hydroperoxidase II expression being entirely dependent on RpoS (Visick & Clarke, 1997). Hydroperoxidase I (HPI) and hydroperoxidase II (HPII) specific activities were measured as described by Visick & Clarke (1997).…”
Section: Methodsmentioning
confidence: 99%
“…Although the basal expression of katG also depends on the RpoS level in stationary phase (30), the katG expression dependent on the OxyR activator may be sufficient to remove FIG. 2.…”
Section: Overproduction Of Polyphosphatase Decreases Poly(p) To Barelmentioning
confidence: 99%